Lean and agile software process improvement in traditional and agile environments. Issue 1 (14th August 2018) - Poth, Alexander; Sasabe, Susumu; Mas, Antònia; Mesquida, Antoni‐Lluís
Abstract: The culture of traditional organizations favors firmly established processes and standardization. Therefore, the adoption of Agile and Lean approaches in these organizations is a challenging issue. This paper presents an overview and outlook of the most well‐known Agile and Lean approaches in order to identify which kind of continuous software process improvement (SPI) is inherent in these approaches. The main objective of this research is to show that Lean and Agile SPI approaches can be pursued depending on the target environment, both in traditional and in agile organizations. Abstract : The culture of traditional organizations favors established processes and standardization. Therefore, the adoption of Agile and Lean approaches in these organizations is a challenging issue. This paper presents an outlook of the most well‐known Agile and Lean approaches in order to identify which kind of continuous software process improvement (SPI) is inherent in these approaches. The objective of this research is to show that Lean and Agile SPI approaches can be pursued both in traditional and in agile organizations.